Circulation in Rapid Hip and Knee Bone Destruction - Nelson, Fred Ritchie Trew (The Journal of Hip Surgery, 2017)
In the hip and knee, the term subchondral insufficiency fracture has been used to describe a focal bone response associated with sudden onset of joint pain, older age, focal osteoporosis, and progression to joint replacement in some cases. Rapidly developing osteoarthritis of the hip is also associated with sudden onset of severe pain, and it usually progresses to larger areas of bone resorption with progression to joint replacement. The literature relative to these three conditions was reviewed focusing on patient demographics, imaging, osteoporosis, associated comorbidities, cytokine changes, similar vascular disorders in other joints, and attempts at nonsurgical treatment. These conditions predominate in, but are not restricted to, individuals who are older than 50, have physical joint abnormalities, are not systemically osteoporotic, and have had no apparent trauma. The biochemical and genetic mechanisms for hip and knee insufficiency fractures is not clear. Although there are reports of hip subchondral insufficiency fractures associated with rapidly developing osteoarthritis of the hip, it is not clear whether all cases are preceded with insufficiency fractures. There is insufficient information on the fracture healing mechanism of insufficiency fractures, and the relationship to vascularity and biochemical imbalance is poorly understood. It is concluded that there are large gaps in the knowledge of biochemical and other mechanisms that might link these conditions. This knowledge may influence nonsurgical treatment strategies.
Keywords: subchondral insufficiency fracture; hip; knee; rapidly developing osteoarthritis; vascularity; cytokine